28 GHz circular polarized fan‐out antenna array with wide‐angle beam‐steering. Issue 3 (2nd December 2021) - Aziz, Imran; Hanning, Johanna; Öjefors, Erik; Wu, Dapeng; Dancila, Dragos
Abstract: The article presents 28 GHz circular polarized antenna arrays designed in an embedded wafer level ball grid array (eWLB) package for 5G applications. The antenna arrays are realized on a re‐distribution layer (RDL) in the fan‐out region of the chip package. Two separate but identical arrays perform RX and TX operations where a crossed dipole is used as a building block of the array. These 4‐element arrays have <−10 dB impedance bandwidth covering 25.3–29.8 GHz (4.5 GHz bandwidth) while presenting 10 dBi maximum realized gain. The measurement results show <3 dB axial ratio in the band 26–29.5 GHz, and the main beam can be steered in ± 50 ∘ in the azimuth plane when array elements are fed by appropriate phases from the chip. The radio frequency module provides 31 dBm maximum equivalent isotropic radiated power (EIRP).